Critical Evaluation of Acetylthiocholine Iodide and Acetylthiocholine Chloride as Substrates for Amperometric Biosensors Based on Acetylcholinesterase - Gabriel-Lucian Radu; Bogdan Bucur; Madalina-Petruta Bucur (Sensors, 2013)
Numerous amperometric biosensors have been developed for the fast analysis of neurotoxic insecticides based on inhibition of cholinesterase (AChE). The analytical signal is quantified by the oxidation of the thiocholine that is produced enzymatically by the hydrolysis of the acetylthiocholine pseudosubstrate. The pseudosubstrate is a cation and it is associated with chloride or iodide as corresponding anion to form a salt. The iodide salt is cheaper, but it is electrochemically active and consequently more difficult to use in electrochemical analytical devices. We investigate the possibility of using acetylthiocholine iodide as pseudosubstrate for amperometric detection. Our investigation demonstrates that operational conditions for any amperometric biosensor that use acetylthiocholine iodide must be thoroughly optimized to avoid false analytical signals or a reduced sensitivity. The working overpotential determined for different screen-printed electrodes was: carbon-nanotubes (360 mV), platinum (560 mV), gold (370 mV, based on a catalytic effect of iodide) or cobalt phthalocyanine (110 mV, but with a significant reduced sensitivity in the presence of iodide anions).